1998
DOI: 10.1080/14626269808567113
|View full text |Cite
|
Sign up to set email alerts
|

The fashion designer in the technological workplace

Abstract: This paper attempts to describe some of the cognitive aspects of a fashion design activity and associate them with a general technological workplace. Within this, a fashion designer is seen as a creative individual who will acquire and utilise knowledge by using her intelligence to form concepts. The research was prompted by the fact that little is published about fashion garment designing; in this it may be paralleled with architectural practice research conducted over 25 years ago. Therefore a theoretical vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…3-D software such as Gerber Technology's APDS-3D Virtual Draping Program has the potential to simulate some aspects of this process, but there is evidence to suggest that designers still need to feel and see the way that fabric is cut and sewn (Jerrard and Bell 1998;Istook 2000). Thus, although there appears to be some experimentation with becoming 'wired', there is also evidence that there is a strong pull for apparel design to remain wired 'in the flesh ' (Learner and Storper 2001: 660).…”
Section: The Role Of Clustering On Product-specific Activitiesmentioning
confidence: 98%
“…3-D software such as Gerber Technology's APDS-3D Virtual Draping Program has the potential to simulate some aspects of this process, but there is evidence to suggest that designers still need to feel and see the way that fabric is cut and sewn (Jerrard and Bell 1998;Istook 2000). Thus, although there appears to be some experimentation with becoming 'wired', there is also evidence that there is a strong pull for apparel design to remain wired 'in the flesh ' (Learner and Storper 2001: 660).…”
Section: The Role Of Clustering On Product-specific Activitiesmentioning
confidence: 98%
“…Although this belief was not shared by the designers or technicians themselves, other studies have suggested that this view may hold some truth for CAD-related design systems. For instance, Jerrard and Bell (1998) interviewed fashion design students to understand the experience of designing both with computer-based tools (CAD) and with mechanical tools (pencil, paper, ruler, and other traditional pattern drafting implements). Their results show that while CAD has the potential to increase efficiency, particularly in calculating and quantitative elements of design, the software felt very restrictive to a lot of the designers.…”
Section: The Effect Of Technological Tools On Design and Creativitymentioning
confidence: 99%
“…Candy (2007) noted that designers must be able to understand how to manipulate the technology to render their ideas. Jerrard and Bell (1998) and Bye and Sohn (2010) both argued that CAD tools can increase efficiency in design; Jerrard and Bell noted that the same tools can restrict usability if the UI is not designed to suit the user's needs or natural workflow, and Bye and Sohn noted that creativity was the responsibility of the designer, despite how efficient the technology. An efficient, intuitive, user-friendly interface that focuses on the user's experience and attempts to streamline the interface to build on already-present tacit knowledge and skills would amplify potential for more widespread digital 3D knit practice, and increase diffusion of this technology among designers.…”
Section: Argument 2a: Improve Knit Design Technology To Eliminate The...mentioning
confidence: 99%
“…Studies that focused on include and experiment with technologies implemented in learning environments, aiming to match the new skills with the market demands and studies in which fashion design or a fashion related subject were the topic chosen to test the technological implementation. (Bertola, 2018;Gu & Liu, 2019;Hodges et al, 2020;Jerrard & Bell, 1998;Jiang & Jin-Hua, 2017;Kazlacheva et al, 2018;Lee et al, 2021;Lu, 2018;Nobile et al, 2021;Petrak et al, 2018;Pires, 2019;Qu, 2018;Spahiu et al, 2021;Surani et al, 2021;White, 2019; CHAPTER II 55 Yezhova et al, 2018;Yick et al, 2018). Finally, when searching for studies that presented or explored alternative theoretical or methodological approaches for fashion design education, very few were included (Ma, 2008(Ma, , 2009Pires, 2019;Reddy, 2014aReddy, , 2014bReddy, , 2016Reddy, , 2017Reddy & Rajaram, 2015).…”
Section: Chapter II 54mentioning
confidence: 99%